Heterogeneous activation of peroxymonosulphate by supported ruthenium catalysts for phenol degradation in water - Muhammad, Syaifullah; Shukla, Pradeep; Tade, Moses; Wang, Shaobin (Elsevier BV, 2012)
Activated carbon (AC) and Zeolite Socony Mobil-5 (ZSM5) supported ruthenium oxide catalysts were prepared and tested to degrade aqueous phenol in the presence of peroxymonosulphate. The physicochemical properties of ruthenium oxide based catalysts were characterised by several techniques such as XRD (X-ray diffraction), SEM-EDS (scanning electron microscopy-energy dispersive X-ray spectroscopy), and N2 adsorption. It was found that RuO2/AC was highly effective in heterogeneous activation of peroxymonosulphate to produce sulphate radicals, presenting higher reaction rate in phenol degradation compared with RuO2/ZSM-5. Degradation efficiency of phenol could be achieved at 100% of phenol decomposition and 60% of total organic carbon (TOC) removal in 1 h at the conditions of 50 ppm phenol, 0.2 g catalyst, 1 g Oxone® in 500 mL solution at 25 °C using the two catalysts. It was also found that phenol degradation was strongly influenced by catalyst loading, phenol concentration, Oxone® concentration and temperature. Kinetic studies proved that a pseudo first order kinetics would fit to phenol decomposition and the activation energies for RuO2/AC and RuO2/ZSM5 were obtained to be 61.4 and 42.2 kJ/mol, respectively.